Politik Hukum Pembentukan Undang-Undang Nomor 27 Tahun 2022 Tentang Pelindungan Data Pribadi - Rizqiyanto, Naufal; Rohman, Azmi Fathu; Raya, Faiz Al-Haq Maulabeta (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Protection of personal data is an issue that is closely related to human rights. The existence of regulations before the establishment of “Undang-Undang Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi” (UU 27/2022) is considered inadequate. The legal politics of forming statutory regulations is urgent to understand so that the intent and purpose of a regulation can be known. Therefore, this normative juridical research seeks to answer the legal politics of the formation of Law 27/2022. The indicators used to analyze the legal politics of establishing are political configuration, “Naskah Akademik”, state ideology, and public participation. The research results show that the legal politics of establishing Law 27/2022 is to form national regulations to protect people's personal data. In the context of political configuration, the PDP Law was proposed by the Government and received approval from parliament. Then the state ideology has been realized in the PDP Law, marked by the existence of state goals and Pancasila values. The public participation process is carried out by involving related parties in Public Hearing Meetings.